2017
DOI: 10.1016/j.apmr.2016.09.115
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Movement Is Not Associated With Objective and Subjective Physical Activity Levels in Chronic Nonspecific Low Back Pain

Abstract: Our data support one aspect of the fear-avoidance model-that higher fear of movement is associated with more disability-but not the aspect of the model linking fear of movement with inactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 42 publications
5
43
2
6
Order By: Relevance
“…The regression results are similar to other studies that found no association between baseline kinesiophobia and baseline pain catastrophizing, and 4-day average total daily activity, 26 but our results indicate a significant negative relationship between baseline kinesiophobia and 4-day average sedentary activity at all times of the day. This important finding suggests that chronic pain patients' activity habits are affected by their baseline level of kinesiophobia and baseline pain catastrophizing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The regression results are similar to other studies that found no association between baseline kinesiophobia and baseline pain catastrophizing, and 4-day average total daily activity, 26 but our results indicate a significant negative relationship between baseline kinesiophobia and 4-day average sedentary activity at all times of the day. This important finding suggests that chronic pain patients' activity habits are affected by their baseline level of kinesiophobia and baseline pain catastrophizing.…”
Section: Discussionsupporting
confidence: 91%
“…Song et al (2012) and Elfving et al (2007) indicate there is a relationship between kinesiophobia, pain catastrophizing, disability, and depression and activity levels, 5,26,27 while Carvalho et al (2017) suggest there is no association. 26 The inconsistency in these results may be due to the methodology of activity measurement. Individuals in chronic pain experience sleep disturbances in the form of varying wake times, several night-time awakenings, poor sleep efficiency, and general insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results of the present study are completely in the line of theoretical assumptions of the theory of reasoned action 14 . In Carvalho's study, people who did not have a good attitude toward physical activity prevented their physical activity 15 . Moreover, in accordance with the present study, numerous studies have revealed that subjective norm has been as the best predictor variable for actual PA [16][17] .…”
Section: Discussionmentioning
confidence: 98%
“…Os exercícios ativos não promoveram redução dos níveis de cinesiofobia em nosso estudo. No entanto, Carvalho et al 25 afirmam que essa não está diretamente associada à inatividade física, indo ao encontro do proposto por Wertli et al, 26 que relatam que fatores psicológicos motivados por crenças equívocas sobre a DL têm papel tão fundamental quanto o sedentarismo e a falta de exercícios físicos no estabelecimento do medo da dor e do movimento em pacientes com DL crônica inespecífica. Sendo assim, a abordagem dos pacientes nessas condições deve estar pautada não somente pela terapia física em si, mas também pela conscientização dos indivíduos sobre as atitudes a serem tomadas no decorrer do tratamento e, principalmente, pela desmistificação de características da DL fundamentadas pelo senso comum ou por evidências ultrapassadas.…”
Section: Discussionunclassified